Effects of dietary L-carnitine on growth performance of nursery pigs - D E Real; M J Rincker; M E Steidinger; S D Carter; K Q Owen; Jim L Nelssen; Robert D Goodband; Michael D Tokach; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2000)
Four experiments were conducted to evaluate the effects of added dietary Lcarnitine on growth performance of nursery pigs. Pigs were fed a control diet containing no added L-carnitine or the control diet with 25, 50, 75, or 100 ppm of added L-carnitine (25, 50, or 100 ppm in Exp. 4). In Exps. 1, 2, and 3 for the overall study, ADG and F/G improved with increasing dietary L-carnitine. In Exp. 4, pigs fed increasing L-carnitine had improved ADG from d 0 to 3 and d 10 to 24. Increasing added carnitine improved F/G from d 10 to 24 and for the overall study. The results suggest that 25 to 50 ppm of added L-carnitine can improve ADG and F/G in nursery pigs. The largest response in pig growth performance was found when carnitine was supplemented to the phase II diet.; Swine Day, Manhattan, KS, November 16, 2000
Keywords: Swine day; 2000; Kansas Agricultural Experiment Station contribution; no. 01-138-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 858; Swine; Carnitine; Nursery pigs; B-vitamin